PELAKSANAAN TUGAS UNIT PELAKSANA TEKNIS DAERAH (UPTD) PENGELOLAAN SAMPAH DAN RUANG TERBUKA HIJAU DALAM PENGELOLAAN SAMPAH DI KECAMATAN MANDAU TAHUN 2023 - Putri, Tara Prisilia Eka; ', Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The implementation of duties by the Technical Implementation Unit (UPTD) for Waste Management is an integral part of efforts to achieve efficient and sustainable waste management in a given region. The main tasks of the UPTD include the collection, transportation, sorting, and processing of waste, carried out using environmentally friendly technologies and systems. In addition, the UPTD plays a role in educating the public about the importance of proper waste management and increasing active citizen participation in waste reduction through recycling and composting programs. In its implementation, the UPTD coordinates with various stakeholders, including local governments and communities, to ensure the smooth operation of waste management processes. The challenges faced include budget constraints, a lack of public awareness, and infrastructure issues. Nevertheless, various innovations and mitigation programs continue to be implemented to address these challenges. The purpose of this study is to understand the role of the UPTD in carrying out waste management in Mandau District. This research employs a qualitative approach, with data collection carried out through observation, interviews, and documentation techniques. Waste management is a process that involves the collection, transportation, sorting, processing, and disposal of waste with the aim of reducing negative impacts on the environment and human health. In this context, effective waste management relies not only on the role of the government but also on public awareness and active participation. Various waste management methods, such as recycling, composting, and the use of environmentally friendly technologies, are increasingly prioritized to reduce the volume of waste reaching the final disposal sites (landfills). Nevertheless, waste management still faces several challenges, including limited facilities, lack of public awareness, and budget limitations. Therefore, an integrated strategy involving government policies, technology, and public education is needed to realize sustainable and environmentally friendly waste management. Keywords: Task Implementation, Waste Management